2012
DOI: 10.4236/nm.2012.31006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neurotransmission by a Specified Oregano Extract Alters Brain Electrical Potentials Indicative of Antidepressant-Like and Neuroprotective Activities

Abstract: Different behavioral states are characterized by distinct patterns of global brain activity. Therefore, the biological effects of herbal extracts on brain functions can be assessed by analyzing the local field potentials, the so-called electropharmacogram analysis. Inspired by our recent findings that a specified oregano extract (OE) exhibited a triple-reuptake activity in vitro, this extract was tested in model of Tele-Stereo-electroencephalogram (EEG) to elucidate how OE affects the electrical brain activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In the same study, the researchers used in vivo microdialysis in rats to confirm that extracellular 5-HT levels were indeed higher after a dose of the oregano extract, albeit more slightly compared with the antidepressant fluoxetine. Moreover, electroencephalogram measurements after acute oral supplementation in freely moving rats showed that this extract may exhibit antidepressant and neuroprotective activities ( 131 ) . Taken together, the results of these studies seem to justify further investigation into possible other dietary sources of monoamine reuptake inhibitors, as well as studies testing whether the beneficial behavioural effects of these plant extracts found in mice can be replicated in human subjects.…”
Section: Triple Monoamine Inhibitorsmentioning
confidence: 99%
“…In the same study, the researchers used in vivo microdialysis in rats to confirm that extracellular 5-HT levels were indeed higher after a dose of the oregano extract, albeit more slightly compared with the antidepressant fluoxetine. Moreover, electroencephalogram measurements after acute oral supplementation in freely moving rats showed that this extract may exhibit antidepressant and neuroprotective activities ( 131 ) . Taken together, the results of these studies seem to justify further investigation into possible other dietary sources of monoamine reuptake inhibitors, as well as studies testing whether the beneficial behavioural effects of these plant extracts found in mice can be replicated in human subjects.…”
Section: Triple Monoamine Inhibitorsmentioning
confidence: 99%